Coronary artery bypass surgery in young adults: excellent perioperative results and long-term survival - Saraiva, J (2019)
OBJECTIVES: To analyse perioperative results, long-term survival and freedom from complications after coronary artery bypass grafting (CABG) in young adults. METHODS: A total of 163 patients, 40 years old or younger, had isolated CABG from January 1989 to December 2010. Pre- and perioperative demographic and clinical data were retrieved from a prospectively organised database. Follow-up data were obtained by letter or telephone interviews. The mean age of the patients was 37.6 ± 2.9 years and 146 were men (90%). Fifty-three patients (32.5%) had angina class III/IV; 106 (65.0%), previous myocardial infarction; and 23 (14.1%), impaired left ventricular function (ejection fraction <40%). Indication for surgery was 3-vessel disease in 101 cases (62.0%), 2-vessel disease in 30 (18.4%) and single-vessel disease in 32 (19.6%). The left main stem was affected in 16 patients (9.8%). The mean EuroSCORE II was 0.92 ± 0.71. A total of 417 grafts were constructed (mean 2.6 grafts/patient), 247 of which (59.2%) were arterial. RESULTS: There were no in-hospital deaths. The mean hospital stay was 7.1 ± 4.0 days. Four patients (2.5%) were lost to follow-up, which extended from 3 to 25 years (mean 15.1 ± 5.5 years). There were 22 late deaths, 72.7% of cardiac or unknown origin. The 5-, 10- and 20-year survival rates were 98.7 ± 10.9, 95.2 ± 1.8 and 79.4 ± 4.4%, respectively. Twenty-six patients (18.1%) had non-fatal cardiac adverse complications (myocardial infarct, percutaneous re-revascularization or class III/IV angina), for 5-, 10- and 20-year freedom from complications of 97.9 ± 1.2, 91.9 ± 2.5 and 65.7 ± 7.1%, respectively. Twenty-two patients (17.5%) needed re-revascularization, for 5-, 10- and 20-year freedom from re-revascularization of 97.6 ± 1.4, 91.9 ± 2.6 and 69.5 ± 6.7%, respectively. CONCLUSIONS: Despite the aggressive nature of coronary artery disease in young patients, perioperative death and morbidity rates are low, with good long-term survival and low rates of re-revascularization.